The Iron Henry: How One Sword Swallower Advanced Modern Medicine. (24th November 2020) - Long, Barry D.; Pine, Harold S.
Abstract : Sword swallowing is an ancient skill that was developed by the fakirs of India and slowly permeated the globe leading up to the late 19th century. Its rise as a popular circus act in Europe coincided with the surge of inventive young minds in the medical community. This crossroad brought about a working relationship between Dr Adolf Kussmaul and a sword swallower named the "Iron Henry." Together, they developed a scope that could be passed through the esophagus for evaluation of disease states from the upper aerodigestive tract all the way to the antrum of the stomach. The unique abilities refined by years of sword swallowing were vital in the work to develop and perform the first successful esophagoscopy and then disseminate the technology. This story should not be forgotten and can give insight into how historical practices and modern invention can come together to great effect.